Antibacterial activity of synthesized 2,4,5-trisubstituted imidazole derivatives - Khan, Mohd Sajid; Siddiqui, Shafi Ahmad; Siddiqui, Mohammad Shaik Rafi Ahmad; Goswami, Usha; Srinivasan, Kumar Venkatraman; Khan, Mohammad Islam (Chemical Biology & Drug Design, 2008)
Some novel chemically synthesized 2,4,5-trisubstituted imidazoles from aryl aldehydes and 1,2-diketones or alpha-hydroxyketone were screened against eight different human pathogenic bacteria and fungi. Seven compounds were found to be active against different bacteria. These compounds showed variation in activity and were found to be active against Gram-positive as well as Gram-negative bacteria. Compound 4-(4,5-diphenyl-1H-imidazol-2-yl)-phenol, 3d was the only compound which showed activity against Klebsiella pneumoniae while rest of the compounds did not show significant activity against this micro-organism. Minimum inhibitory concentrations of the compounds were in the range of 0.50 to 6.1 mu g/mL and minimum bactericidal concentration ranges from 1.11 to 12.9 mu g/mL. The candidature of active compounds to be an effective and novel drug was examined based on Lipinski's rule of Five which explained ClogP, LogS, H-bond acceptors, H-Bond donors and rotational bonds. Compounds 3a-d and 3f satisfies Lipinski's rule of Five and could be proposed as potent new antibacterial drugs.
Keywords: 1; 2; 2-Diketones; 4; 5-trisubstituted imidazoles; alpha-hydroxyketone; antibacterial activity; aryl aldehydes